SIR‐HUXt—A Particle Filter Data Assimilation Scheme for CME Time‐Elongation Profiles - Luke Barnard; Mathew Owens; Chris Scott; Matthew Lang; Mike Lockwood (Space Weather, 2023)
Abstract We present SIR‐HUXt, the integration of a sequential importance resampling data assimilation scheme with the HUXt solar wind model. SIR‐HUXt assimilates the time‐elongation profiles of Coronal Mass Ejection (CME) fronts in the low heliosphere, like those extracted from heliospheric imager (HI) data. Observing System Simulation Experiments are used to explore SIR‐HUXt's performance for a simple synthetic CME scenario of an Earth directed CME in a uniform solar wind, where the CME is initialized with the average CME speed and width. These experiments are performed for a range of observer locations, from 20° to 90° behind Earth, spanning the L5 point where ESA's Vigil mission will return HI data for operational space weather forecasting. For this idealized scenario, SIR‐HUXt performs well at constraining the CME speed, and has some success at constraining the CME longitude while the CME width is largely unconstrained by SIR‐HUXt. Rank‐histograms suggest the SIR‐HUXt ensembles are well calibrated, with no indications of bias or under/over dispersion. Improved constraints on the initial CME speed lead to improvements in the CME transit time and arrival speed. For an L5 observer, SIR‐HUXt reduced the transit time and arrival speed uncertainties by 69% and 63%. Therefore, SIR‐HUXt could improve the real‐world representivity of HUXt simulations and reduce the uncertainty of CME arrival time forecasts. The idealized scenario studied here likely enhances SIR‐HUXt's performance relative to the challenge of simulating real‐world CMEs and solar wind conditions. Future work should validate SIR‐HUXt with case studies of real CMEs in structured solar wind.